Various Approaches and Applications of Artificial Intelligence in Preventing and Detecting Diseases - Kumar, Kotha Kranthi; Nasar I, Sheik (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
Artificial Intelligence (AI) is increasingly being applied in the advancement of disease prevention and early detection in recent times. The basic concept of artificial intelligence is imitating human intellect in the sense that it can execute tasks, detect patterns, or forecast events via learning from data gathered from diverse sources. It can analyze a lot of medical information, like images and records, to find patterns and identify risks for different diseases. This helps doctors diagnose and treat illnesses sooner, improving morbidity and mortality. Additionally, AI can analyze data from diverse sources like social media and travel patterns to predict and track disease outbreaks, helping public health officials take preventative measures and mitigate the spread of infections. The article explores various approaches and applications of artificial intelligence in preventing and detecting diseases across different medical domains.